Liver abscess due to Klebsiella pneumoniae in a healthy 12-year-old boy - Da Hye Yoon; Yeon Jin Jeon; E Young Bae; Dae Chul Jeong; Jin Han Kang (Korean Pediatric Society, 2013)
Pyogenic liver abscess (PLA) is rare in healthy children. We report a case of PLA in an immunocom petent 12yearold boy. Percutaneous catheter drainage was performed for the abscess. In addition, parenteral antibiotics were administered for 3 weeks. Klebsiella pneumoniae was detected in the culture of blood and drained fluid. Here, we present this case and a brief review of the literature on this subject.